ДОКАЗАТЕЛЬНАЯ МЕДИЦИНА - СТУПЕНЬКА ВВЕРХ ПО ЛЕСТНИЦЕ ПОЗНАНИЯ ИЛИ ДВИЖЕНИЕ ПО КРУГУ? - В. С. Хазов (SINAPS LLC, 2012)
From the author's viewpoint, the theoretical basis of modern medical science and practice is out of date. Once progressive method of clinical and anatomical mapping and classic physiology do not move advance medicine forward. Evidence-based medicine, which is also a product of the basic methods, explores the "horizontal" field of science. The top of medicine in the form of the etiology and pathogenesis of the total of any disease remains elusive. The author proposes to achieve this objective to apply the method of system analysis, in particular, the theory of functional systems of academician P.K. Anokhin.